A method for pre-welding surface treatment of a pure molybdenum powder metallurgy part diffusion welding

By pretreatment methods that form nickel and nickel-phosphorus layers on the surface of pure molybdenum powder metallurgy parts, the problem of high-quality bonding in diffusion welding of pure molybdenum powder metallurgy parts is solved, achieving high-strength and high-airtightness welding effects at low temperatures, which is suitable for nuclear fusion devices and electronic packaging.

CN122687205BActive Publication Date: 2026-11-06CHENGDU RUNBO TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611194621.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-11-06
Estimated Expiration
2046-08-07

AI Technical Summary

Technical Problem

Due to the high melting point and low diffusion coefficient of pure molybdenum powder metallurgy parts, direct diffusion welding is difficult to achieve high-quality bonding, and the post-weld airtightness does not meet the stringent requirements of fields such as nuclear fusion and electronic packaging.

Method used

After activation treatment on the surface of pure molybdenum powder metallurgy parts, a nickel layer and a nickel-phosphorus layer are formed. The nickel layer serves as an intermediate transition layer, and the nickel-phosphorus layer serves as a low-melting-point metal intermediate layer. Instantaneous liquid phase diffusion welding is formed through chemical plating to reduce the diffusion welding temperature and ensure the interface contact area and bonding force.

Benefits of technology

It achieves high-quality bonding at temperatures below 1700℃, resulting in high joint strength and good sealing after welding, meeting the hermeticity requirements of nuclear fusion devices and electronic packaging, and avoiding problems such as grain coarsening and recrystallization embrittlement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122687205B_ABST
    Figure CN122687205B_ABST
Patent Text Reader

Abstract

The application discloses a surface pretreatment method before diffusion welding of pure molybdenum powder metallurgy parts, and relates to the technical field of surface treatment and welding of powder metallurgy parts. The method comprises the following steps: performing surface activation treatment on the pure molybdenum powder metallurgy part to be treated; forming a nickel layer on the surface of the pure molybdenum powder metallurgy part after the surface activation treatment; and forming a nickel-phosphorus layer on the surface of the nickel layer of the pure molybdenum powder metallurgy part. The application forms an activation layer, a nickel layer and a nickel-phosphorus layer on the surface of the pure molybdenum in sequence, uses the nickel-phosphorus layer as a low-melting-point metal interlayer for diffusion welding, utilizes the high diffusion coefficient of nickel and the characteristic of phosphorus in reducing eutectic temperature, significantly reduces the temperature required for diffusion welding, avoids the grain coarsening and recrystallization embrittlement of the pure molybdenum powder metallurgy part, simultaneously improves the interface contact and atomic interdiffusion, greatly improves the sealing performance of the welded joint, and is suitable for high-end fields such as nuclear fusion devices and electronic packaging which have strict requirements on air tightness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of surface treatment and welding of powder metallurgy parts, and in particular to a method for pre-treatment of the surface before diffusion welding of pure molybdenum powder metallurgy parts. Background Technology

[0002] Molybdenum (Mo), a refractory metal, possesses a high melting point (2623℃), good high-temperature strength, and low vapor pressure. High-purity molybdenum (≥99.99% molybdenum content) plays an irreplaceable role in cutting-edge fields such as nuclear fusion devices, aerospace, and electronic packaging. Particularly in the field of nuclear fusion, molybdenum's high-temperature mechanical properties, thermal and electrical conductivity, high sputtering threshold, and low tritium retention rate make it a key material for plasma facing components (PFCs). For example, the first wall of the EAST (Experimental Advanced Superconducting Tokamak) fully superconducting tokamak device is made of pure molybdenum.

[0003] However, molybdenum is a difficult-to-machine material. Its high hardness, high strength, and low plasticity make it prone to chipping during cutting, resulting in discontinuous cutting and making surface roughness control difficult, thus affecting machining accuracy. Simultaneously, molybdenum has poor thermal conductivity, with its thermal conductivity coefficient only about one-third that of copper. Cutting heat tends to concentrate at the tool tip, accelerating tool wear, and heat dissipation is slow, increasing the risk of workpiece deformation. Furthermore, molybdenum hardens rapidly during machining, increasing its hardness by 30% to 50%, which further increases the difficulty of subsequent cutting and significantly raises quality risks.

[0004] In bonding (such as diffusion welding), molybdenum has a high melting point of 2623°C, and atomic diffusion requires extremely high activation energy. At typical diffusion welding temperatures (approximately 0.5–0.7 times the melting point), molybdenum has a very low bulk diffusion coefficient, making atomic migration difficult. Direct diffusion welding of pure molybdenum requires temperatures above 1700°C to achieve effective bonding, but this leads to grain coarsening and recrystallization embrittlement. Furthermore, molybdenum has a strong affinity for oxygen, forming a stable MoO3 oxide film when heated in air. This oxide film sublimates at approximately 800°C, but the sublimation process leaves a rough surface and can cause contamination. If pre-weld treatment is inadequate, this oxide film becomes a fatal barrier to diffusion welding.

[0005] For certain high-end products manufactured using molybdenum materials, the performance requirements are extremely stringent. For example, the first wall cooling plate and accelerator electrode plates in nuclear fusion devices have dense cooling channels inside, with a gap of only about 1 mm between the channels and the hole walls. These products typically need to withstand a pressure test of 2.2 MPa without leakage after welding, and the leak rate requirement for helium mass spectrometry leak detection is less than 2 × 10⁻⁶. -10 Pa·m 3 / s. Processing deformation or poor welding quality can both lead to leaks, resulting in failure to meet leak rate testing standards. Existing processing and welding technologies struggle to simultaneously address the machinability of molybdenum materials, weld quality, and such stringent sealing performance requirements. Furthermore, even after precision machining, pure molybdenum powder metallurgy parts inevitably possess microscopic irregularities, porosity, and work-hardened layers on the surfaces to be welded. Direct diffusion welding results in a small actual contact area, leading to numerous unbonded voids at the weld interface, severely impacting the joint's mechanical properties and airtightness. Current processes struggle to achieve full contact and adequate diffusion bonding at lower temperatures. Summary of the Invention

[0006] This application discloses a surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts, in order to solve the technical problem in the related art that pure molybdenum powder metallurgy parts have high melting point and low diffusion characteristics, making it difficult to achieve high-quality bonding through direct diffusion welding, and the post-weld airtightness does not meet the requirements for use in fields such as nuclear fusion and electronic packaging.

[0007] To solve the above problems, this application adopts the following technical solution: In a first aspect, embodiments of this application provide a surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts, comprising the following steps: The pure molybdenum powder metallurgy parts to be processed undergo surface activation treatment; A nickel layer is formed on the surface of a pure molybdenum powder metallurgy part after surface activation treatment; A nickel-phosphorus layer is formed on the surface of the nickel layer in a pure molybdenum powder metallurgy part.

[0008] The technical solutions adopted in the embodiments of this application can achieve the following beneficial effects: (1) The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts provided in this application first activates the pure molybdenum substrate before the formation of the nickel layer, effectively removing the surface oxide film and improving the surface activity, providing a substrate with good activity for the subsequent formation of the nickel layer, ensuring that the nickel layer can be deposited uniformly and has a satisfactory bonding force with the molybdenum substrate; then, by using the nickel layer on the activated pure molybdenum substrate as an intermediate transition layer, a substrate with good bonding force and uniformity is provided for the subsequent electroless nickel-phosphorus plating, thereby avoiding the process obstacles caused by the difficulty of forming a qualified plating layer directly on pure molybdenum due to electroless nickel-phosphorus plating.

[0009] (2) The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts provided in this application forms a nickel-phosphorus layer on the surface of a nickel layer. This nickel-phosphorus layer serves as a low-melting-point metal intermediate layer for transient liquid phase diffusion welding, while the nickel layer acts as a substrate, providing a uniform and complete deposition surface for the nickel-phosphorus layer. Utilizing the characteristic that nickel in the nickel-phosphorus layer is much lower than that of molybdenum, and the effect of phosphorus further lowering the solidus temperature, the nickel-phosphorus layer melts first during the diffusion welding process to form a transient liquid phase. The method of this application enables effective bonding of transient liquid phase diffusion welding within the range of 1180℃ to 1200℃, which is about 500℃ lower than the 1700℃ or higher required for direct diffusion welding of pure molybdenum. This effectively suppresses grain coarsening and recrystallization embrittlement of pure molybdenum powder metallurgy parts, maintaining the fine-grained structure and mechanical properties of the powder metallurgy state.

[0010] (3) The pre-welding surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts provided in this application produces a nickel-phosphorus layer with good surface coverage and density. During the diffusion welding heating and pressurization process, the low-melting-point nickel-phosphorus layer melts first to form a transient liquid phase, which can fully fill the microscopic irregularities and pores on the surface of the pure molybdenum powder metallurgy parts, increasing the actual contact area of ​​the welding interface to nearly 100%, and creating sufficient contact conditions for atomic diffusion in the subsequent isothermal solidification process. The presence of the nickel layer ensures that the nickel-phosphorus layer can uniformly and completely cover the substrate, thereby fully exerting the above-mentioned filling effect.

[0011] (4) The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts provided in this application embodiment has a high diffusion coefficient of nickel in molybdenum within the nickel-phosphorus layer. At the instantaneous liquid phase diffusion welding temperature, the nickel-phosphorus layer melts to form a liquid phase, and the nickel atoms in the liquid phase diffuse significantly into the pure molybdenum base material on both sides, causing a change in the liquid phase composition, increasing the melting point, and guiding isothermal solidification, ultimately forming a continuous and stable Ni(Mo) solid solution transition layer. This transforms the originally difficult-to-weld "molybdenum-molybdenum" homogeneous interface into a "molybdenum-nickel" heterogeneous interface with a greater diffusion driving force. The transition layer is metallurgically bonded to both the pure molybdenum powder metallurgy part and the final solidified structure, resulting in a high overall joint strength and good sealing performance.

[0012] (5) The pure molybdenum powder metallurgy parts treated by the pre-weld surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts provided in the embodiments of this application have been experimentally proven to withstand a pressure test of 2.2 MPa after welding without any leakage, and the leakage rate detected by helium mass spectrometry can be stably lower than 2 × 10⁻⁶. -10 Pa·m 3 / s. This airtightness index fully meets the most stringent requirements for the airtightness of molybdenum welding in cutting-edge fields such as nuclear fusion devices (plasma-facing components and internal cooling structures in tokamak devices such as EAST) and electronic packaging (hermetically sealed housings for high-power devices). In particular, for complex thin-walled components with dense internal cooling channels and a gap of only about 1 mm between the channels and the hole walls, the method of this application can achieve reliable sealing welding without clogging the channels or causing deformation, solving the long-standing technological problem of "difficulty in achieving both machinability and sealing" for such components.

[0013] (6) The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts provided in this application forms a nickel layer and a nickel-phosphorus layer on the molybdenum surface in sequence. The nickel layer serves as the substrate and the nickel-phosphorus layer serves as the key low-melting-point intermediate layer for instantaneous liquid phase diffusion welding. It is smoothly connected with the subsequent instantaneous liquid phase diffusion welding process, the process parameters are controllable, the operation window is wide, and it has good reproducibility and industrial application prospects. Attached Figure Description

[0014] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0015] Figure 1 This is a schematic diagram of the structure of the first sample used in the embodiments and comparative examples of this application; Figure 2 This is a schematic diagram of the structure of the second sample used in the embodiments and comparative examples of this application; Figure 3 This is a schematic diagram of the welding area of ​​the first specimen used in the embodiments and comparative examples of this application.

[0016] In the figure: 100, first sample; 101, first plate; 102, main flow channel groove; 103, first process hole; 104, branch flow channel groove; 105, air inlet; 106, exhaust hole; 200, second sample; 201, second plate; 202, second process hole. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be described in detail below. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments in this application, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0018] The terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and not to describe a specific order or sequence. It should be understood that such use of data can be interchanged where appropriate so that embodiments of this application can be implemented in orders other than those illustrated or described herein, and the objects distinguished by "first," "second," etc., are generally of the same class and the number of objects is not limited; for example, a first object can be one or more. Furthermore, in the specification and claims, "and / or" indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship.

[0019] In related technologies, pure molybdenum powder metallurgy parts, due to their high melting point and low diffusion coefficient, face difficulties in atomic migration during direct diffusion welding. Effective bonding requires temperatures above 1700℃. However, high temperatures can lead to grain coarsening and recrystallization embrittlement, resulting in poor weld joint quality. This fails to meet the requirements of nuclear fusion, electronic packaging, and other fields where post-weld leakage rates (≤2×10⁻⁶) are low. -10 Pa·m 3 It meets stringent requirements for pressure resistance (2.2MPa without leakage) and pressure resistance ( / s).

[0020] The inventive concept of this application is as follows: Before diffusion welding of pure molybdenum powder metallurgy parts, the surface of the parts is pretreated. First, the pure molybdenum substrate is activated to remove the surface oxide film and improve surface activity. Then, a nickel layer is formed on the pure molybdenum substrate, followed by a nickel-phosphorus layer. The nickel-phosphorus layer is formed by electroless plating. Since electroless nickel-phosphorus plating cannot directly form a uniform, complete, and well-bonded layer on the pure molybdenum substrate, the role of this nickel layer is to provide an intermediate transition layer for the subsequent electroless nickel-phosphorus plating. The activation treatment provides a substrate with good activity for the flash-plated nickel layer, ensuring that the nickel layer can be deposited uniformly and with sufficient adhesion. The composite intermediate layer composed of the above-mentioned nickel layer and nickel-phosphorus layer is used as a low-melting-point metal intermediate layer for instantaneous liquid phase diffusion welding.

[0021] Specifically, nickel's melting point is much lower than molybdenum's, and the introduction of phosphorus further lowers the solidus temperature of the nickel-phosphorus alloy, allowing the nickel-phosphorus layer to form a transient liquid phase at the welding temperature. During the diffusion welding heating process, the nickel-phosphorus layer melts first at a temperature much lower than molybdenum's melting point, forming a liquid phase. On one hand, this liquid phase fills the microscopic irregularities and pores on the molybdenum surface, increasing the actual contact area of ​​the welding interface to nearly 100%. On the other hand, nickel atoms in the liquid phase undergo significant solid-state diffusion into the pure molybdenum base materials on both sides, driving the isothermal solidification process and forming a continuous Ni(Mo) solid solution transition layer at the interface. This transition layer transforms the originally difficult-to-weld "molybdenum-molybdenum" homogeneous interface into a "molybdenum-nickel" heterogeneous interface with greater diffusion driving force, thereby achieving high-quality metallurgical bonding. Throughout the process, the pure molybdenum powder metallurgy part remains solid and does not melt, while the nickel-phosphorus intermediate layer, as a low-melting-point component, forms a transient liquid phase and is completely eliminated through isothermal solidification. This is a typical characteristic of transient liquid phase diffusion welding. Meanwhile, since the connection temperature of this method (1180℃~1200℃) is much lower than the temperature required for pure molybdenum to be directly solid-phase diffusion welded (usually above 1700℃), it is reduced by about 500℃, thereby avoiding grain coarsening and recrystallization embrittlement of pure molybdenum powder metallurgy parts.

[0022] The following is in conjunction with the appendix Figures 1 to 3 This paper provides a detailed description of a surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts, based on specific embodiments and application scenarios.

[0023] This application provides a surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts, comprising the following steps: The pure molybdenum powder metallurgy parts to be processed undergo surface activation treatment; A nickel layer is formed on the surface of a pure molybdenum powder metallurgy part after surface activation treatment; A nickel-phosphorus layer is formed on the surface of the nickel layer in a pure molybdenum powder metallurgy part.

[0024] In some embodiments, the thickness of the nickel-phosphorus layer is 12.5 μm-18 μm. It is understood that the thickness of the nickel-phosphorus layer is one of the key parameters affecting the quality of diffusion welding. If the thickness is too small (below 12.5 μm), the transient liquid phase formed by the nickel-phosphorus interlayer cannot fully fill the microscopic irregularities and pores on the surface of the pure molybdenum powder metallurgy part, resulting in insufficient actual contact area at the interface and difficulty in forming effective metallurgical bonding in local areas, thus becoming a leakage channel in subsequent pressure testing or leak detection. If the thickness is too large (above 18 μm), on the one hand, it will introduce too much low-melting-point alloy phase, generating excessive liquid phase flow during the diffusion welding heating and pressurization process, which may cause internal cracking or elemental segregation of the coating itself. On the other hand, an excessively thick nickel-phosphorus layer will change the overall compositional distribution of the joint area, causing excessive enrichment of nickel atoms and an excessively thick solid solution transition layer with molybdenum, which may reduce the shear strength of the joint. Therefore, by controlling the thickness of the nickel-phosphorus layer within the above-mentioned reasonable range, the surface defects of the pure molybdenum powder metallurgy parts can be fully filled through liquid phase flow, and sufficient nickel atoms with high diffusion coefficient can be provided to form a continuous and stable Ni(Mo) solid solution transition layer. At the same time, the negative effects of an excessively thick intermediate layer are avoided, thereby ensuring that the diffusion weld joint has excellent sealing performance and mechanical strength.

[0025] In some embodiments, the thickness of the nickel layer is 1.5 μm to 3 μm.

[0026] In some embodiments, the mass fraction of phosphorus in the nickel-phosphorus layer is 8%-10%. It is understood that the phosphorus content is one of the key factors affecting the diffusion welding effect of the nickel-phosphorus layer. If the phosphorus content is too low (<8%), the solidus temperature of the nickel-phosphorus alloy is too high, and the effect of reducing the welding temperature is not significant. During diffusion welding, the nickel-phosphorus layer is difficult to melt at a lower temperature to form a sufficient liquid phase, limiting its effect on filling microscopic defects at the interface and promoting atomic diffusion. The welding temperature still needs to be maintained at a high level, which cannot effectively prevent grain coarsening and recrystallization embrittlement of pure molybdenum powder metallurgy parts. If the phosphorus content is too high (>10%), although the solidus temperature is further reduced, the brittleness of the nickel-phosphorus layer itself increases, leading to a decrease in the toughness of the coating. Brittle cracking may occur during pre-weld clamping or post-weld cooling. Simultaneously, excessive brittle phase residue in the joint area reduces the shear strength and impact resistance of the diffusion weld joint, which is detrimental to obtaining a highly reliable sealing joint. Therefore, by controlling the mass fraction of phosphorus within the above-mentioned reasonable range, the diffusion welding temperature can be effectively reduced by forming a nickel-phosphorus alloy with a low solidus temperature (approximately 500°C lower than that of direct solid-phase diffusion welding of pure molybdenum). This also avoids the adverse effects of excessive brittleness on the mechanical properties of the joint, while ensuring that the nickel-phosphorus layer has good liquid phase flow capability and good interfacial interdiffusion behavior during the diffusion welding process, thereby achieving a balance between high sealing performance and high strength in the diffusion welded joint.

[0027] In some embodiments, the nickel-phosphorus layer is formed by electroless plating. The plating solution is prepared with pure water and contains nickel sulfate heptahydrate and sodium hypophosphite. The concentration of nickel sulfate heptahydrate is 30 g / L to 35 g / L, and the concentration of sodium hypophosphite is 25 g / L to 30 g / L. It is understood that nickel sulfate heptahydrate provides nickel ions as the main salt, while sodium hypophosphite provides phosphorus as a reducing agent. The concentration ratio of the two directly affects the deposition rate, phosphorus content, and coating quality. Controlling the concentrations of nickel sulfate heptahydrate and sodium hypophosphite within the ranges of 30 g / L to 35 g / L and 25 g / L to 30 g / L, respectively, ensures a moderate deposition rate, uniform and stable composition, and yields a nickel-phosphorus layer with suitable phosphorus content (8%-10% by mass), low internal stress, and good adhesion, providing a high-quality intermediate transition layer for subsequent diffusion welding.

[0028] In some embodiments, the electroless plating solution further contains sodium citrate, sodium acetate, and thiourea. The concentration of sodium citrate is 10 g / L to 15 g / L, the concentration of sodium acetate is 15 g / L to 20 g / L, and the concentration of thiourea is 0.5 mg / L to 1.5 mg / L. It is understood that sodium citrate and sodium acetate act as a complexing agent and a buffer, respectively, to stabilize the plating solution and adjust the pH value. Sodium citrate can form a stable complex with nickel ions, preventing the formation of nickel hydroxide precipitate under alkaline conditions and slowing down the deposition rate to obtain a dense coating. By controlling the concentration of the above additives within the aforementioned reasonable range, a stable plating solution system and a high-quality nickel-phosphorus layer can be obtained.

[0029] In some embodiments, the electroless plating process conditions are as follows: the pH value of the plating solution is 4.8 to 5.2, adjusted with ammonia; the temperature of the plating solution is 90°C to 92°C; and the plating time is 60 min to 80 min.

[0030] In some embodiments, the nickel layer is a flash-plated nickel layer, formed by an electroplating process. The electroplating solution is prepared with pure water and contains nickel chloride and hydrochloric acid. The concentration of nickel chloride is 250 g / L to 350 g / L, and the concentration of hydrochloric acid is 4 g / L to 6 g / L. It is understood that nickel chloride, as the main salt, provides nickel ions, and its concentration directly affects the deposition rate and density of the coating. The role of hydrochloric acid is to inhibit the hydrolysis of nickel ions, prevent the formation of nickel hydroxide precipitate, and simultaneously improve the conductivity of the plating solution and the anodic dissolution efficiency.

[0031] In some embodiments, the electroplating process conditions are as follows: a reverse plating treatment is performed at a temperature of 20–30°C before electroplating, and the reverse plating current density is 1 A / dm². 2 ~2A / dm 2 The reverse plating time is 0.5 min to 1 min; Then, forward electroplating is performed at a temperature of 20–30°C and a current density of 6 A / dm². 2 ~8A / dm 2 The electroplating time is 1 to 2 minutes, resulting in an average thickness of 1.5 μm to 2.5 μm for the flash-plated nickel layer. It is understood that the reverse plating process involves applying a reverse current before forward electroplating. Its function is to polarize the cathode to the anode, electrochemically dissolving and removing the extremely thin oxide film and adsorption layer remaining on the surface of the pure molybdenum powder metallurgy part, while simultaneously reactivating the surface and improving the adhesion of the subsequent flash-plated nickel. By controlling the reverse plating parameters, forward plating current density, and time within the aforementioned range, a dense and uniform flash-plated nickel layer with a thickness of 1.5 μm to 2.5 μm and good adhesion to the pure molybdenum powder metallurgy part can be obtained, providing a reliable intermediate transition substrate for subsequent electroless nickel-phosphorus plating.

[0032] In some embodiments, the activation treatment uses an activation solution prepared with pure water, containing hydrochloric acid and hexamethylenetetramine. The concentration of hydrochloric acid is 150 g / L to 250 g / L, and the concentration of hexamethylenetetramine is 3 g / L to 5 g / L. The activation treatment process conditions are: immersion at room temperature for 0.5 min to 1 min. It is understood that hydrochloric acid is used to remove the oxide film and passivation layer from the surface of the pure molybdenum powder metallurgy parts and to activate them, while hexamethylenetetramine acts as a corrosion inhibitor to prevent excessive corrosion of the surface of the pure molybdenum powder metallurgy parts.

[0033] In some embodiments, a water washing step is included after the activation treatment of the pure molybdenum powder metallurgy parts. For example, the water washing step after surface activation treatment involves immersing the parts in running pure water at room temperature for 10-15 seconds, and then removing them. It is understood that after activation treatment, the surface of the pure molybdenum powder metallurgy parts retains acidic activation liquid and dissolved products. If not thoroughly cleaned, the residual liquid will contaminate the subsequent flash nickel plating solution, leading to changes in the solution composition and decreased stability, and may also cause localized over-corrosion or hydrogen embrittlement. Water washing can thoroughly remove surface residues, ensuring the purity of the plating solution and the adhesion of the coating.

[0034] In some embodiments, a water rinsing step is included after the formation of the nickel layer; for example, the water rinsing step after the formation of the nickel layer is: immersing in room temperature flowing pure water for 10-15 seconds, and then removing it. It is understood that after the flash-plated nickel layer is formed, the workpiece surface retains plating solution components (nickel chloride, hydrochloric acid, etc.) and adsorbates produced by the hydrogen evolution side reaction. If not cleaned in time, the residual plating solution will dry and crystallize, affecting the purity and stability of the plating solution during subsequent electroless nickel-phosphorus plating, and potentially causing surface contamination of the nickel layer, reducing the adhesion of the nickel-phosphorus layer. Immersing in room temperature flowing pure water for 10-15 seconds can sufficiently dilute and remove residues without causing oxidation or passivation of the nickel layer surface due to excessive immersion time. Flowing water helps to quickly renew the interface solution, improving cleaning efficiency. This water rinsing step provides a clean and active nickel layer surface for subsequent electroless nickel-phosphorus plating.

[0035] In some embodiments, a water washing step and a drying step are included after the formation of the nickel-phosphorus layer. For example, the water washing step after forming the nickel-phosphorus layer is as follows: immersion in room temperature pure water for 5-8 seconds, then removal; then immersion in room temperature flowing pure water for 10-15 seconds, then removal. The drying step is as follows: first, the surface of the pure molybdenum powder metallurgy part is dried using clean compressed air; then, at intervals not exceeding 60 minutes, it is placed in a vacuum oven for drying at a temperature of 200℃-220℃ for 2-3 hours; after drying, it is cooled to room temperature under vacuum and removed from the oven. It is understood that after chemically plating the nickel-phosphorus layer, the surface of the pure molybdenum powder metallurgy part retains plating solution components (nickel salts, sodium hypophosphite, complexing agents, etc.). A two-step water washing process is used: first, static pure water immersion for 5-8 seconds to dilute and remove most of the residual plating solution; then, flowing pure water immersion for 10-15 seconds for further thorough cleaning. Static immersion reduces the amount of flowing water used, while flowing immersion enhances the removal effect. The two methods work together to achieve efficient cleaning in a short time, preventing residue from drying and forming spots or affecting subsequent processes. During drying, clean compressed air is used to quickly remove surface water and prevent water stains. The requirement of an interval of no more than 60 minutes is to avoid prolonged exposure of the workpiece to humid air, which could lead to surface oxidation or dust adsorption. Then, a vacuum oven is used to dry the workpiece at 200℃~220℃ for 2~3 hours. The purpose is threefold: first, to thoroughly remove moisture from the interior of the plating layer and the micropores of the pure molybdenum powder metallurgy parts; second, to eliminate hydrogen that may have been adsorbed during the electroless plating process (although electroless nickel-phosphorus plating uses sodium hypophosphite as a reducing agent, there is still a certain degree of hydrogen evolution side reaction), preventing hydrogen atoms from accumulating at grain boundaries and hindering the interdiffusion of nickel and molybdenum atoms during subsequent diffusion welding; and third, the vacuum environment prevents oxidation of the nickel-phosphorus layer and the pure molybdenum powder metallurgy parts at high temperatures. Cooling the workpiece to room temperature with the furnace reduces thermal stress and ensures the bonding strength between the plating layer and the pure molybdenum powder metallurgy parts. During drying, ordinary ovens should be avoided because their oxygen-containing atmosphere will cause the nickel-phosphorus layer to oxidize and discolor at high temperatures, and may even affect its performance as an intermediate layer for diffusion soldering.

[0036] In some embodiments, the process includes surface cleaning of the pure molybdenum powder metallurgy parts before activation treatment. This surface cleaning process comprises: organic solvent wiping, a first water wash, ultrasonic chemical degreasing, a second water wash, electrochemical degreasing, a third water wash, water film continuity inspection, dust removal, and a fourth water wash. It is understood that pure molybdenum powder metallurgy parts, due to their manufacturing process (powder pressing, sintering) and subsequent machining, often have various contaminants adhering to their surfaces: including heavy oil stains such as cutting fluid and rust-preventive oil; fine powder particles and dust; carbon black or oxides that may remain from the sintering process; and metal debris introduced during processing. If not thoroughly removed, these contaminants will hinder the direct contact between the activation solution and the molybdenum matrix of the pure molybdenum powder metallurgy parts, leading to uneven activation or even complete failure to activate in some areas. This, in turn, affects the adhesion and uniformity of subsequent flash-plated nickel and electroless nickel-phosphorus plating layers, ultimately reducing the sealing performance and mechanical strength of the diffusion weld joint.

[0037] Specifically, the specific operation methods and functions of each step in the surface cleaning process are as follows: Organic solvent cleaning: All holes and flow channels of pure molybdenum powder metallurgy parts are cleaned using a stiff nylon brush immersed in anhydrous ethanol to remove the loose dust layer generated during the machining process. Simultaneously, the strong dissolving power of anhydrous ethanol on grease is utilized to initially remove oil and highly adhesive contaminants from the surface of the pure molybdenum powder metallurgy parts through wiping, laying the foundation for large-area cleaning. The choice of organic solvent is not limited to anhydrous ethanol; volatile solvents with good oil-dissolving capabilities, such as acetone, are also suitable. The appropriate solvent should be selected based on the type of contaminant and site conditions.

[0038] First water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 5-10 seconds, then remove them; remove the oil stains and residual solvents dissolved or softened by organic solvents by soaking and changing the water (or gently stirring) to prevent the re-adsorption of contaminants.

[0039] After the first water wash, the pure molybdenum powder metallurgy parts are hung up and then proceed to the next process. Titanium alloy hooks are used for hanging, ensuring the flow channels on the pure molybdenum powder metallurgy parts are perpendicular to the horizontal plane. The purpose of using titanium alloy hooks is to reduce the introduction of metallic impurities from the electroplating nickel bath and the electroless low-phosphorus nickel plating bath, avoiding a decrease in coating adhesion due to impurity contamination.

[0040] Ultrasonic chemical degreasing: Pure molybdenum powder metallurgy parts are immersed in a chemical degreasing solution, and ultrasonic waves are applied. The chemical degreasing solution is prepared using pure water and contains 30g / L–50g / L sodium hydroxide, 20g / L–40g / L sodium carbonate, and 20g / L–40g / L trisodium phosphate. The process conditions for ultrasonic chemical degreasing are: temperature controlled at 30℃–40℃, time 3min–4min; and ultrasonic process parameters are: frequency 40kHz–60kHz, power density 20W / L–30W / L. The cavitation effect of ultrasound generates microjets and shock waves that can penetrate deep into the micropores, pits, and crevices on the surface of the pure molybdenum powder metallurgy parts, peeling off grease and particulate matter adsorbed in the microstructure, achieving deep cleaning. Compared to simple chemical degreasing, ultrasonic-assisted degreasing significantly improves the cleaning effect on complex shapes and porous surfaces of powder metallurgy parts. Understandably, sodium hydroxide provides an alkaline environment, saponifying animal and vegetable oils; sodium carbonate acts as a buffer and emulsifier, stabilizing the pH value; and trisodium phosphate has the functions of emulsifying, dispersing, and softening hard water. Too low a concentration results in insufficient degreasing ability, while too high a concentration can easily cause excessive surface corrosion or residual alkali. A temperature of 30–40℃ ensures degreasing efficiency while avoiding the thermal impact of high temperatures on pure molybdenum powder metallurgy parts; a treatment time of 3–4 minutes allows for thorough cleaning without excessive corrosion.

[0041] Second water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 5-10 seconds, then remove them to remove the residual degreasing liquid and stripped contaminants after ultrasonic chemical degreasing; then immerse the pure molybdenum powder metallurgy parts in room temperature running pure water for 5-10 seconds, then remove them to further thoroughly clean the residue and ensure that there are no degreasing liquid components on the surface.

[0042] Electrochemical degreasing: Pure molybdenum powder metallurgy parts are placed in an electrolyte as the anode for degreasing. The electrolyte consists of sodium hydroxide and pure water, with the sodium hydroxide concentration ranging from 30 g / L to 50 g / L. The electrochemical degreasing process conditions are: temperature 30℃ to 40℃, and current density 2 A / dm³. 2 ~5A / dm 2The processing time is 2-3 minutes. After energization, a large number of oxygen bubbles are generated on the anode surface. The generation and rising of these bubbles exert a strong mechanical stripping effect on the surface adsorbates. Simultaneously, the chemical action of the electrolyte further saponifies or emulsifies residual grease. Electrochemical degreasing can remove stubborn oil films that are difficult to remove with chemical degreasing and has a slight activation effect on the surface of pure molybdenum powder metallurgy parts. It is understandable that this process only uses anodic degreasing and not cathodic degreasing or alternating anode and cathode degreasing. The reason is that during cathodic degreasing, the pure molybdenum powder metallurgy part acts as the cathode, and hydrogen bubbles will be precipitated on its surface (hydrogen ions are reduced to hydrogen gas). Some hydrogen atoms may penetrate into the crystal lattice of the pure molybdenum powder metallurgy part and accumulate at the grain boundaries. Pure molybdenum has a certain adsorption and diffusion capacity for hydrogen. The infiltrated hydrogen atoms can form hydrogen bubbles or cause hydrogen embrittlement during subsequent high-temperature diffusion welding. This leads to micro-pressure concentration at the weld interface and occupies grain boundary sites, hindering the mutual diffusion of nickel and molybdenum atoms. Consequently, an unwelded area (false weld) forms at the interface, severely reducing the sealing performance and mechanical strength of the weld joint. Anodic degreasing avoids this hydrogen atom infiltration problem. Furthermore, a sodium hydroxide concentration of 30–50 g / L provides sufficient alkalinity and conductivity, and a temperature of 30–40°C is beneficial for improving degreasing efficiency. The aforementioned anodic degreasing process can thoroughly remove oil stains while avoiding the risk of hydrogen atom infiltration.

[0043] The third water rinse: Thoroughly cleans the residual electrolyte and contaminants after electrochemical degreasing, ensuring no new ionic impurities are introduced to the surface. Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 2-5 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 2-5 seconds, then remove them. By first statically immersing to dilute and remove most of the residual alkali, and then further enhancing the cleaning effect with flowing pure water immersion, the two consecutive water rinses can achieve efficient cleaning in a very short time (4-10 seconds in total), avoiding oxidation or rusting of the pure molybdenum powder metallurgy parts due to excessive cleaning time, while also preventing electrolyte components from being carried into subsequent processes.

[0044] Water film continuity inspection: Immerse the cleaned pure molybdenum powder metallurgy parts in pure water and then remove them to observe the integrity of the surface water film. A clean metal surface has good hydrophilicity; the water film should be continuous, uniform, and without breaks or agglomeration. If oil or hydrophobic contaminants remain on the surface, the water film will break and form water droplets. Visual inspection should show that the water film does not break continuously for 30 seconds, indicating that the oil has been thoroughly removed. If this is not met, repeat the organic solvent wiping, first water rinse, ultrasonic chemical degreasing, second water rinse, electrochemical degreasing, and third water rinse process. This inspection method is quick and intuitive, used to verify whether the cleaning effect meets the requirements.

[0045] Descaling: After the above-mentioned chemical and electrochemical degreasing, a thin and loose layer of "dust" may remain on the surface of the pure molybdenum powder metallurgy parts. The descaling process involves immersing the pure molybdenum powder metallurgy parts in a mixed acid solution. This mixed acid solution is prepared with pure water and contains 100g / L–150g / L of nitric acid and 100g / L–150g / L of sulfuric acid. The descaling process conditions are: treatment at room temperature for 0.5min–1min. Utilizing the strong oxidizing effect of nitric acid and the dissolving effect of sulfuric acid, the dust is removed through acid dissolution and complexation reactions, restoring the metallic color of the pure molybdenum powder metallurgy parts. Room temperature conditions and a short treatment time of 0.5–1min are sufficient to remove the loose surface dust while avoiding excessive acid etching. A fourth water rinse should be performed immediately after descaling to prevent acid residue.

[0046] Fourth water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 5-8 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 5-8 seconds, then remove them and immediately proceed to the next process. By first statically immersing and diluting the acid solution, and then rinsing with flowing water to enhance the removal effect, the two consecutive water washes can achieve surface neutralization of the pure molybdenum powder metallurgy parts in a very short time (total 10-16 seconds), avoiding the adverse effects of acid residue on subsequent activation treatment and coating adhesion.

[0047] The aforementioned multi-step progressive cleaning process, from coarse to fine and from physical to chemical, is progressive and complementary, resulting in a molybdenum surface with extremely high cleanliness, free of oil and dust. This creates ideal conditions for subsequent activation treatment, thereby ensuring the bonding quality of the diffusion welding intermediate layer and the overall weld airtightness.

[0048] The following specific embodiments illustrate in detail a surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts provided in this application.

[0049] The pure molybdenum powder metallurgy specimens used in the following examples and comparative examples are partial structures of accelerator electrode sheets (molybdenum content ≥ 99.99%) (hereinafter referred to as "the specimens"). The specimens are provided with multiple process holes, flow channels, and inlet holes 105 and outlet holes 106, etc. The minimum distance between each process hole and the flow channel wall is only about 1 mm (the number can be reduced according to the size, but the spacing remains 1 mm), which can reflect the welding difficulties and airtightness requirements of the actual electrode sheet. At the same time, this specimen has extremely high requirements for welding airtightness (leakage rate ≤ 2 × 10⁻⁶). -10 Pa·m 3 / s), and welding deformation and weld rate must be strictly controlled after welding.

[0050] Furthermore, the surface roughness of the sample must reach Ra≤1.6μm, the parallelism and flatness must both be less than 0.03mm, and all surfaces should be free of scratches and dents. In summary, this sample imposes extremely stringent requirements on surface pretreatment.

[0051] I. Structural Description of Pure Molybdenum Powder Metallurgy Parts 1. First sample 100 Please see Figure 1 The first sample 100 includes a first plate 101, and the welding surface of the first plate 101 is provided with a flow channel groove structure. Both sides of the first plate 101 are provided with a main flow channel groove 102, and ten branch flow channel grooves 104 are evenly arranged in the middle of the first plate 101. The two ends of each branch flow channel groove 104 are respectively connected to the main flow channel grooves 102 on both sides.

[0052] A first process hole 103 is provided between two adjacent branch flow channel grooves 104. The first process hole 103 is a circular through hole that extends along the thickness direction of the plate. The distance a between the first process hole 103 and the adjacent branch flow channel groove 104 is 1 mm; the distance b between the main flow channel groove 102 and the edge of the first plate 101 is 1 mm.

[0053] The first plate 101 is also provided with an air inlet 105 and an exhaust outlet 106. The air inlet 105 and the exhaust outlet 106 are respectively connected to the main flow channel 102 on the corresponding side, serving as fluid inlet and outlet channels. Please refer to Figure 3 The blue area on the first plate 101 is the welding area.

[0054] 2. Second sample 200 Please see Figure 2 The second sample 200 includes a second plate 201, which is completely matched with the overall shape and dimensions of the first plate 101. The second plate 201 has an array of second process holes 202, which are circular through holes that extend along the thickness of the plate. The diameter and arrangement of the second process holes 202 correspond one-to-one with those of the first process holes 103.

[0055] 3. Post-welding flow channel structure The first sample 100 and the second sample 200 are aligned and bonded together, and welding is completed along the blue welding area around the first plate 101 to form an integrated welded part. After welding, a main flow channel is formed between the main flow channel 102 on the first plate 101 and the second plate 201, and each branch flow channel 104 is formed between the branch flow channel 104 and the second plate 201; the main flow channel and each branch flow channel are interconnected to form a complete flow channel system, forming ten independent branch flow channels, and there is no crossflow between the branch flow channels.

[0056] The air inlet 105 and the exhaust 106 are connected to the external pipeline through the main flow channels on both sides. After welding, the distance between the first process hole 103 and the branch flow channel is maintained at 1 mm, the distance between the main flow channel and the edge of the first plate 101 is maintained at 1 mm, and there is no offset in the position of each structure.

[0057] II. Implementation Examples Example 1:

[0058] A method for surface pretreatment before diffusion welding of pure molybdenum powder metallurgy parts, comprising the following steps in sequence: Step S10: Organic solvent cleaning. All holes and flow channels of the pure molybdenum powder metallurgy parts are cleaned using a hard nylon brush immersed in anhydrous ethanol to remove the loose dust layer generated during the machining process. Simultaneously, utilizing the strong dissolving power of anhydrous ethanol for grease, oil stains and highly adhesive contaminants on the surface of the pure molybdenum powder metallurgy parts are initially removed by wiping.

[0059] Step S20: First water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 10 seconds, and then take them out.

[0060] Step S30: Mounting. When mounting, use titanium alloy hooks and keep the branch flow channel groove 104 on the pure molybdenum powder metallurgy part perpendicular to the horizontal plane.

[0061] Step S40: Ultrasonic chemical degreasing. The pure molybdenum powder metallurgy part is immersed in a chemical degreasing solution, and ultrasonic waves at a frequency of 50 kHz and a power density of 25 W / L are applied for ultrasonic chemical degreasing. The chemical degreasing solution is prepared using pure water and contains: 40 g / L sodium hydroxide, 30 g / L sodium carbonate, and 30 g / L trisodium phosphate. The process parameters for ultrasonic chemical degreasing are: temperature 35℃ and time 3.5 min.

[0062] Step S50: Second water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 10 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 10 seconds, then remove them.

[0063] Step S60: Electrochemical degreasing. The pure molybdenum powder metallurgy part is placed in an electrolyte as the anode for degreasing. The electrolyte consists of sodium hydroxide and pure water, with a sodium hydroxide concentration of 40 g / L. The process parameters for electrochemical degreasing are: temperature 35℃, current density 3.5 A / dm³. 2 The processing time is 2.5 minutes.

[0064] Step S70: Third water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 2 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 5 seconds, then remove them.

[0065] Step S80: Water film continuity check. Immerse the cleaned pure molybdenum powder metallurgy parts in pure water and then take them out. Observe the integrity of the surface water film. If the water film does not break for 30 seconds, it means that the oil stains have been cleaned. If it does not meet the requirements, repeat steps S10-S70.

[0066] Step S90: Remove the ash residue by acid washing: Immerse the pure molybdenum powder metallurgy parts that have passed the water film continuity inspection into a mixed acid solution; the mixed acid solution is prepared from pure water and contains 125g / L of nitric acid and 125g / L of sulfuric acid. The process conditions for removing the ash residue are: treatment at room temperature for 1 min.

[0067] Step S100: Fourth water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 5 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 8 seconds, then remove them.

[0068] Step S110: Activation: Immerse the pure molybdenum powder metallurgy parts in an activation treatment solution for activation treatment. The activation treatment solution is prepared with pure water and contains 200 g / L hydrochloric acid and 4 g / L hexamethylenetetramine. The activation treatment process conditions are: immersion at room temperature for 0.8 min. Step S120: Fifth water wash: Immerse the activated pure molybdenum powder metallurgy parts in room temperature running pure water for 15 seconds, and then take them out.

[0069] Step S130: Flash plating of a nickel layer, formed using an electroplating process. The electroplating solution is prepared from pure water and contains 300 g / L nickel chloride and 5 g / L hydrochloric acid. The electroplating process conditions are as follows: a reverse plating treatment is performed at 25°C before electroplating, with a reverse plating current density of 1.5 A / dm³. 2 The reverse plating time is 1 minute; then forward plating is performed at a temperature of 25℃ and a current density of 7 A / dm³. 2 The electroplating time is 1.5 min, which makes the average thickness of the flash-plated nickel layer reach about 2.2 μm (detected by a thickness gauge).

[0070] Step S140: Sixth water wash: Immerse the activated pure molybdenum powder metallurgy parts in room temperature running pure water for 15 seconds, and then take them out.

[0071] Step S150: Electroless nickel-phosphorus plating: The plating solution is prepared with pure water and contains 33 g / L nickel sulfate heptahydrate, 28 g / L sodium hypophosphite, 12 g / L sodium citrate, 18 g / L sodium acetate, and 1 mg / L thiourea. The electroless plating process conditions are: pH value of the plating solution 5.0, adjusted and controlled with ammonia; plating solution temperature 91℃; plating time 70 min.

[0072] Step S160: Seventh water wash: Immerse the pure molybdenum powder metallurgy part after nickel-phosphorus plating in room temperature pure water for 8 seconds, and then take it out; then immerse the workpiece in room temperature flowing pure water for 15 seconds, and then take it out.

[0073] Step S170: Drying. First, use clean compressed air to dry the surface of the pure molybdenum powder metallurgy part; then immediately put it into a vacuum oven for drying at a temperature of 210°C for 2.5 hours; after drying, cool it to room temperature under vacuum and remove it from the oven to obtain the surface-pretreated pure molybdenum powder metallurgy part.

[0074] Example 2:

[0075] The difference between this embodiment and embodiment 1 is that in step S150, when performing electroless nickel-phosphorus plating, the sodium hypophosphite in the plating solution is 25 g / L. The rest is the same as in Example 1, and a pure molybdenum powder metallurgy part with surface pretreatment is obtained.

[0076] Example 3:

[0077] The difference between this embodiment and embodiment 1 is that in step S150, when performing electroless nickel-phosphorus plating, the sodium hypophosphite in the plating solution is 30 g / L. The rest is the same as in Example 1, and a pure molybdenum powder metallurgy part with surface pretreatment is obtained.

[0078] Example 4:

[0079] The difference between this embodiment and embodiment 1 is that in step S150, the electroless nickel-phosphorus plating time is 60 minutes. The rest is the same as in Example 1, and a pure molybdenum powder metallurgy part with surface pretreatment is obtained.

[0080] Example 5:

[0081] The difference between this embodiment and embodiment 1 is that in step S150, the electroless nickel-phosphorus plating time is 80 minutes. The rest is the same as in Example 1, and a pure molybdenum powder metallurgy part with surface pretreatment is obtained.

[0082] Example 6:

[0083] A method for surface pretreatment before diffusion welding of pure molybdenum powder metallurgy parts, comprising the following steps in sequence: Step S10: Organic solvent cleaning. All holes and flow channels of the pure molybdenum powder metallurgy parts are cleaned using a hard nylon brush immersed in anhydrous ethanol to remove the loose dust layer generated during the machining process. Simultaneously, utilizing the strong dissolving power of anhydrous ethanol for grease, oil stains and highly adhesive contaminants on the surface of the pure molybdenum powder metallurgy parts are initially removed by wiping.

[0084] Step S20: First water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 5 seconds, and then take them out.

[0085] Step S30: Mounting. When mounting, use titanium alloy hooks and keep the branch flow channel groove 104 on the pure molybdenum powder metallurgy part perpendicular to the horizontal plane.

[0086] Step S40: Ultrasonic chemical degreasing. The pure molybdenum powder metallurgy parts are immersed in a chemical degreasing solution, and ultrasonic waves with a frequency of 60 kHz and a power density of 30 W / L are applied for ultrasonic chemical degreasing. The chemical degreasing solution is prepared using pure water and contains: 50 g / L sodium hydroxide, 20 g / L sodium carbonate, and 35 g / L trisodium phosphate. The process parameters for ultrasonic chemical degreasing are: temperature 40℃ and time 3 min.

[0087] Step S50: Second water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 8 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 8 seconds, then remove them.

[0088] Step S60: Electrochemical degreasing. The pure molybdenum powder metallurgy part is placed in an electrolyte as the anode for degreasing. The electrolyte consists of sodium hydroxide and pure water, with a sodium hydroxide concentration of 30 g / L. The process parameters for electrochemical degreasing are: temperature 30℃, current density 2 A / dm³. 2 The processing time is 3 minutes.

[0089] Step S70: Third water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 3 seconds, and then take them out; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 3 seconds, and then take them out.

[0090] Step S80: Water film continuity check. Immerse the cleaned pure molybdenum powder metallurgy parts in pure water and then take them out. Observe the integrity of the surface water film. If the water film does not break for 30 seconds, it means that the oil stains have been cleaned. If it does not meet the requirements, repeat steps S10-S70.

[0091] Step S90: Remove the ash residue using acid washing: Immerse the pure molybdenum powder metallurgy parts that have passed the water film continuity inspection into a mixed acid solution; the mixed acid solution is prepared from pure water and contains 100g / L nitric acid and 150g / L sulfuric acid. The process conditions for removing the ash residue are: treatment at room temperature for 1 min.

[0092] Step S100: Fourth water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 7 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 6 seconds, then remove them.

[0093] Step S110: Activation: Immerse the pure molybdenum powder metallurgy parts in an activation treatment solution for activation treatment. The activation treatment solution is prepared with pure water and contains 150 g / L hydrochloric acid and 3 g / L hexamethylenetetramine. The activation treatment process conditions are: immersion at room temperature for 0.5 min. Step S120: Fifth water wash: Immerse the activated pure molybdenum powder metallurgy parts in room temperature running pure water for 15 seconds, and then take them out.

[0094] Step S130: Flash plating of a nickel layer, formed using an electroplating process. The electroplating solution is prepared from pure water and contains 350 g / L nickel chloride and 4 g / L hydrochloric acid. The electroplating process conditions are as follows: a reverse plating treatment is performed at 30°C before electroplating, with a reverse plating current density of 1 A / dm³. 2 The reverse plating time is 0.5 min; then forward plating is performed at a temperature of 30℃ and a current density of 6 A / dm². 2 The electroplating time is 1 minute, so that the average thickness of the flash-plated nickel layer reaches about 1.5 μm (detected by a thickness gauge).

[0095] Step S140: Sixth water wash: Immerse the activated pure molybdenum powder metallurgy parts in room temperature running pure water for 15 seconds, and then take them out.

[0096] Step S150: Electroless nickel-phosphorus plating: The plating solution is prepared with pure water and contains 35 g / L nickel sulfate heptahydrate, 25 g / L sodium hypophosphite, 15 g / L sodium citrate, 20 g / L sodium acetate, and 1.5 mg / L thiourea. The electroless plating process conditions are: pH value of the plating solution 4.8, adjusted and controlled with ammonia; plating solution temperature 92℃; plating time 80 min.

[0097] Step S160: Seventh water wash: Immerse the pure molybdenum powder metallurgy part after nickel-phosphorus plating in room temperature pure water for 8 seconds, and then take it out; then immerse the workpiece in room temperature flowing pure water for 10 seconds, and then take it out.

[0098] Step S170: Drying. First, use clean compressed air to dry the surface of the pure molybdenum powder metallurgy part; then immediately put it into a vacuum oven for drying at 200°C for 3 hours; after drying, cool it to room temperature under vacuum and remove it from the oven to obtain the surface-pretreated pure molybdenum powder metallurgy part.

[0099] Example 7:

[0100] A method for surface pretreatment before diffusion welding of pure molybdenum powder metallurgy parts, comprising the following steps in sequence: Step S10: Organic solvent cleaning. All holes and flow channels of the pure molybdenum powder metallurgy parts are cleaned using a hard nylon brush immersed in anhydrous ethanol to remove the loose dust layer generated during the machining process. Simultaneously, utilizing the strong dissolving power of anhydrous ethanol for grease, oil stains and highly adhesive contaminants on the surface of the pure molybdenum powder metallurgy parts are initially removed by wiping.

[0101] Step S20: First water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 5 seconds, and then take them out.

[0102] Step S30: Mounting. When mounting, use titanium alloy hooks and keep the branch flow channel groove 104 on the pure molybdenum powder metallurgy part perpendicular to the horizontal plane.

[0103] Step S40: Ultrasonic chemical degreasing. The pure molybdenum powder metallurgy part is immersed in a chemical degreasing solution, and ultrasonic waves at a frequency of 40 kHz and a power density of 20 W / L are applied for ultrasonic chemical degreasing. The chemical degreasing solution is prepared using pure water and contains: 30 g / L sodium hydroxide, 40 g / L sodium carbonate, and 25 g / L trisodium phosphate. The process parameters for ultrasonic chemical degreasing are: temperature 30℃ and time 4 min.

[0104] Step S50: Second water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 10 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 5 seconds, then remove them.

[0105] Step S60: Electrochemical degreasing. The pure molybdenum powder metallurgy part is placed in an electrolyte as the anode for degreasing. The electrolyte consists of sodium hydroxide and pure water, with a sodium hydroxide concentration of 50 g / L. The process parameters for electrochemical degreasing are: temperature 40℃, current density 5 A / dm³. 2 The processing time is 2 minutes.

[0106] Step S70: Third water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 5 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 2 seconds, then remove them.

[0107] Step S80: Water film continuity check. Immerse the cleaned pure molybdenum powder metallurgy parts in pure water and then take them out. Observe the integrity of the surface water film. If the water film does not break for 30 seconds, it means that the oil stains have been cleaned. If it does not meet the requirements, repeat steps S10-S70.

[0108] Step S90: Remove the ash residue using acid washing: Immerse the pure molybdenum powder metallurgy parts that have passed the water film continuity inspection into a mixed acid solution; the mixed acid solution is prepared from pure water and contains 150g / L nitric acid and 100g / L sulfuric acid. The process conditions for removing the ash residue are: treatment at room temperature for 0.5min.

[0109] Step S100: Fourth water wash: Immerse the pure molybdenum powder metallurgy parts in room temperature pure water for 8 seconds, then remove them; then immerse the pure molybdenum powder metallurgy parts in room temperature flowing pure water for 5 seconds, then remove them.

[0110] Step S110: Activation: Immerse the pure molybdenum powder metallurgy parts in an activation treatment solution for activation treatment. The activation treatment solution is prepared with pure water and contains 250 g / L hydrochloric acid and 5 g / L hexamethylenetetramine. The activation treatment process conditions are: immersion at room temperature for 0.5 min. Step S120: Fifth water wash: Immerse the activated pure molybdenum powder metallurgy parts in room temperature running pure water for 10 seconds, and then take them out.

[0111] Step S130: Flash plating of a nickel layer, formed using an electroplating process. The electroplating solution is prepared from pure water and contains 250 g / L nickel chloride and 6 g / L hydrochloric acid. The electroplating process conditions are as follows: a reverse plating treatment is performed at 20°C before electroplating, with a reverse plating current density of 2 A / dm³. 2 The reverse plating time is 1 minute; then forward plating is performed at a temperature of 20℃ and a current density of 8 A / dm³. 2 The electroplating time is 2 minutes, so that the average thickness of the flash-plated nickel layer reaches about 2.5 μm (detected by a thickness gauge).

[0112] Step S140: Sixth water wash: Immerse the activated pure molybdenum powder metallurgy parts in room temperature running pure water for 10 seconds, and then take them out.

[0113] Step S150: Electroless nickel-phosphorus plating: The plating solution is prepared with pure water and contains 30 g / L nickel sulfate heptahydrate, 30 g / L sodium hypophosphite, 10 g / L sodium citrate, 15 g / L sodium acetate, and 0.5 mg / L thiourea. The electroless plating process conditions are: pH value of the plating solution 4.8, adjusted and controlled with ammonia; plating solution temperature 90℃; plating time 70 min.

[0114] Step S160: Seventh water wash: Immerse the pure molybdenum powder metallurgy part after nickel-phosphorus plating in room temperature pure water for 8 seconds, and then take it out; then immerse the workpiece in room temperature flowing pure water for 10 seconds, and then take it out.

[0115] Step S170: Drying. First, use clean compressed air to dry the surface of the pure molybdenum powder metallurgy part; then immediately put it into a vacuum oven for drying at a temperature of 220°C for 2 hours; after drying, cool it to room temperature under vacuum and remove it from the oven to obtain the surface-pretreated pure molybdenum powder metallurgy part.

[0116] III. Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that steps S110-160 are omitted, and activation, flash plating of nickel layer and electroless nickel-phosphorus layer are not performed. The rest is the same as in Example 1, resulting in a pure molybdenum powder metallurgy part with a cleaned surface.

[0117] Comparative Example 2: The difference between this comparative example and Example 1 is that in step S150, an aminosulfonate nickel plating solution system is used for electroplating to form an aminosulfonate nickel layer (which is also a pure nickel layer) on the surface of the flash-plated nickel layer; so that the average total thickness of the nickel layer formed by the flash-plated nickel layer and the aminosulfonate nickel layer is 18.54 μm. The rest is the same as in Example 1, and a pure molybdenum powder metallurgy part with surface pretreatment is obtained.

[0118] Comparative Example 3: The difference between this comparative example and Example 1 is that steps S130 and 140 are omitted, and a flash nickel plating layer is not performed. The rest is the same as in Example 1, and a pure molybdenum powder metallurgy part with surface pretreatment is obtained.

[0119] Comparative Example 4: The difference between this comparative example and Example 1 is that steps S110 and 120 are omitted, and activation is not performed. The rest is the same as in Example 1, and a pure molybdenum powder metallurgy part with surface pretreatment is obtained.

[0120] Comparative Example 5: The difference between this comparative example and Example 1 is that in step S130, when flash plating the nickel layer, reverse plating is not performed, and forward electroplating is performed directly. The rest is the same as in Example 1, and a pure molybdenum powder metallurgy part with surface pretreatment is obtained.

[0121] IV. Experimental Examples: In the following tests on coating appearance, coating thickness, and adhesion, the pure molybdenum powder metallurgy parts used were all the first sample 100, and their structure is as follows: Figure 1 , Figure 3As shown, it includes a first plate 101, a main flow channel 102, a branch flow channel 104, a first process hole 103, an air inlet 105, and an exhaust hole 106. The sample in the groove is made of the same material and has the same surface pretreatment process as the workpiece to be welded, ensuring that its surface pretreatment conditions are completely consistent with those of the workpiece to be welded.

[0122] 1. Coating appearance: 1.1 Observation Method: Visual observation was used, supplemented by a standard light source light box (color temperature 6500K) to provide uniform illumination. Three samples were taken for each example and comparative example. The pure molybdenum powder metallurgy parts of Examples 1 to 7 and Comparative Examples 2 to 5, after surface pretreatment, were placed in the light box, and the coating surface was visually inspected at a 45° angle from a distance of about 30cm from the sample surface. The observation included the integrity of the coating, the uniformity of color, and the presence of surface defects such as roughness, delamination, peeling, flaking, streaky coating, and scratches.

[0123] 1.2 Observation results: as shown in Table 1 below.

[0124] 2. Coating thickness inspection: 2.1 Detection Method: The coating thickness was determined using X-ray fluorescence spectroscopy. The specific procedure was as follows: Pure molybdenum powder metallurgy parts with surface pretreatment obtained in Examples 1 to 7 and Comparative Examples 2 to 5 were used as test samples. Three samples were taken from each example and comparative example. The coating thickness (including the total thickness of the nickel and nickel-phosphorus layers) was measured along the vertical direction of the sample using an X-ray fluorescence coating thickness gauge. At least five different locations (four points evenly distributed around the center and perimeter) were measured for each sample, and the arithmetic mean was taken as the thickness value of that sample. The arithmetic mean of the thickness values ​​of the three samples from that example / comparative example was then taken as the final coating thickness.

[0125] 2.2 The test results are shown in Table 1 below.

[0126] 3. Bonding strength test: 3.1 Detection Method: The adhesion between the plating layers (including nickel and nickel-phosphorus layers) and the pure molybdenum substrate was tested using the in-tank thermal shock method. Three in-tank samples were used for each example and comparative example. The specific testing steps are as follows: (1) Heating: The samples after the tank treatment in Examples 1 to 7 and Comparative Examples 2 to 5 were placed in an oven and kept at 200±10℃ for 30 minutes; (2) Sudden cooling: After taking out the sample, immediately immerse it in room temperature water for rapid cooling. After cooling to room temperature, take it out and observe the coating surface. (3) Judgment: Take out the sample and visually inspect the coating surface. If the coating has no blistering, peeling, or cracking, the adhesion is deemed to be qualified; otherwise, if any of the above defects are present, it is deemed to be unqualified.

[0127] 3.2 The test results are shown in Table 1 below.

[0128] Table 1. Coating test results

[0129] As shown in Table 1: Examples 1-7: Using the complete scheme of this application, all three samples were free of blistering, peeling, and cracking. The coatings were complete and uniform, without defects such as roughness, delamination, or peeling. This is because: the activation treatment removed the surface oxide film of the pure molybdenum substrate, providing a highly active substrate for subsequent flash nickel plating; the reverse plating treatment during flash nickel plating further activated the coating, enhancing the adhesion between the nickel layer and the substrate; the nickel layer, as an intermediate transition layer, provided a uniform and complete deposition surface for electroless nickel-phosphorus plating, avoiding the process obstacle of direct nickel-phosphorus plating; the thickness and phosphorus content of the nickel-phosphorus layer were within the optimal range, ensuring the instantaneous liquid phase required for subsequent diffusion welding while avoiding an increase in brittle phases (such as Ni3P) and a decrease in coating toughness due to excessive phosphorus content. Therefore, these examples can stably obtain composite coatings with excellent adhesion, compliant thickness, and complete appearance.

[0130] Comparative Example 2 (nickel-phosphorus layer replaced with nickel sulfamate layer, i.e., only nickel plating): The total thickness of the nickel layer was controlled to 18.54 μm through process control. At this time, the plating met the requirements in terms of adhesion, thickness, and appearance. However, due to the lack of a low-melting-point nickel-phosphorus layer, whether this nickel layer can achieve effective diffusion welding in the temperature range of 1180℃~1200℃, and whether the sealing performance and mechanical properties of the welded joint meet the requirements, all need further verification.

[0131] Comparative Example 3 (omitting the flash nickel plating layer, directly electroless nickel-phosphorus plating): thickness 17.41 μm, but all three samples showed blistering and peeling. The reason is that without a nickel layer as a transition substrate, the electroless nickel-phosphorus plating had extremely poor adhesion when directly deposited on the pure molybdenum surface, and all failed after thermal shock.

[0132] Comparative Example 4 (activation treatment omitted): Thickness 17.83 μm, 1 out of 3 samples showed blistering and peeling. The incomplete removal of the oxide film on the surface of the unactivated pure molybdenum led to a decrease in the adhesion of the nickel layer, which in turn affected the quality of the nickel-phosphorus layer, resulting in defects in some samples.

[0133] Comparative Example 5 (reverse plating treatment omitted during flash nickel plating): Thickness 17.49 μm, one of the three samples showed slight blistering (no peeling). The reverse plating treatment itself has an activating effect; omitting it results in slightly weaker adhesion between the nickel layer and the substrate, leading to insufficient local adhesion of the nickel-phosphorus layer and slight defects after thermal shock.

[0134] In summary, the activation treatment, flash nickel plating (including reverse plating), and electroless nickel-phosphorus plating in this application are synergistic and indispensable. The comparative examples, due to the omission of any key step or uncontrolled parameters, could not simultaneously obtain coatings with high adhesion, suitable thickness, and complete appearance.

[0135] 4. Diffusion welding was performed on the pure molybdenum powder metallurgy parts with surface pretreatment obtained in Comparative Example 1, Examples 1-7, and Comparative Examples 2-5. Multiple sets of welding were performed in each example and comparative example (i.e., multiple sets of independent samples were welded to obtain multiple welded parts, which were in the same batch and process as the samples used for coating detection). Ultrasonic C-scan detection, air tightness test and helium mass spectrometry detection were performed on each welded part.

[0136] 4.1 Diffusion welding method: Using the surface-pretreated pure molybdenum powder metallurgy parts obtained in Comparative Example 1, Examples 1 to 7, and Comparative Examples 2 to 5 as base materials (wherein the examples and some comparative examples have formed nickel and nickel-phosphorus layers on the surface), instantaneous liquid phase diffusion welding was performed according to the following steps: (1) Surface cleaning: Use acetone and a lint-free cloth to wipe and clean the surface of the base material. During cleaning, the environment should be kept clean to avoid impurities adhering to the surface of the workpiece.

[0137] (2) Assembly: The plating layers of two pure molybdenum powder metallurgy parts (first sample 100 and second sample 200) that have undergone the same surface pretreatment are brought together so that the nickel-phosphorus layers on the surfaces of the two pure molybdenum powder metallurgy parts are in direct contact, forming a "nickel-phosphorus layer-nickel-phosphorus layer" docking structure, and the whole part is placed in a vacuum diffusion welding furnace.

[0138] (3) Vacuuming: Vacuum the furnace cavity until the vacuum pressure is no greater than 2×10⁻⁶. -2 The temperature begins to rise after Pa.

[0139] (4) Heating and pressurization: Heating is carried out at a rate of 5℃ / min to 1190℃, while maintaining an initial pressure of 2t during the heating process; when the temperature reaches 1190℃, the pressure is increased to 60t, and a vacuum is simultaneously drawn to ensure that the vacuum pressure inside the vacuum diffusion welding equipment does not exceed 1×10 -3 Pa; hold at 1190℃ and 60t for 90min; after holding, cool with the furnace until the temperature drops below 200℃, then remove the welded parts, cool to room temperature and then perform welding quality inspection.

[0140] It should be noted that in this application, the unit "t" used to express pressure refers to ton-force, that is, the gravity generated by an object with a mass of 1 ton under standard gravitational acceleration. Its conversion relationship with the legal unit of measurement is common knowledge in the field, 1t≈9.8kN.

[0141] 4.2 Welding quality inspection, inspection methods and results are as follows: (1) Ultrasonic C-scan detection: Experimental Method: Ultrasonic C-scan nondestructive testing was used to inspect the diffusion weld joint. Water immersion coupling was employed, using deionized water as the coupling medium. The workpiece under inspection was placed in a water tank, and the probe position was adjusted so that the acoustic beam focus was located at the weld interface. Before inspection, reference echo signals were acquired in a defect-free area of ​​the workpiece (e.g., the base material), and a baseline sensitivity was set. During scanning, the probe moved along a set path in the weld interface area, acquiring echo amplitude information at each location. The amplitude distribution image of the weld interface was generated using C-scan imaging software. Areas with echo amplitudes below the baseline threshold were defined as incomplete or weakly bonded defects. The following indicators were calculated using the C-scan images: ① Welding rate: The proportion of the area of ​​the effective welded area in the welded interface to the total area of ​​the welded interface.

[0142] ② Overall defect rate: The proportion of the total area of ​​all defects (unwelded, pores, inclusions, etc.) in the entire workpiece (including welding interface, flow channel, hole and base material) to the total area of ​​the workpiece.

[0143] ③ Defect ratio in flow channels and holes: The proportion of the area of ​​defects existing in the flow channels and holes on the workpiece to the total area of ​​the entire workpiece.

[0144] For each embodiment and comparative example, three welded parts were tested, and the average value of the test results of the three welded parts was taken as the corresponding test result.

[0145] Experimental results are shown in Table 2 below.

[0146] Taking Example 1 as an example, its average welding rate was 96.06%, the average overall defect rate was 29.36%, and the average defect rate in the flow channel and hole area was 25.43%.

[0147] Data verification: The average non-welded rate was calculated to be 3.94% from the average weld rate of 96.06%; the average overall defect rate of 29.36% minus the average proportion of defects in the flow channel and void areas of 25.43% yields 3.93%, which is basically consistent with the above. This indicates that, apart from defects in the flow channel and void areas, the remaining defects in the overall defect rate are mainly non-welded defects at the weld interface, verifying the consistency of the test data.

[0148] (2) Air tightness test: Experimental Method: Using nitrogen as the medium, the air inlet 105 of the welded component was sealed to the gas source pipeline, and the exhaust port 106 was sealed with a plug. Nitrogen was introduced into the internal flow channel system of the welded component, and the pressure was increased to the test pressure of 2.5 MPa. This pressure was maintained at room temperature for 2 hours, and the system pressure drop was monitored in real time using a pressure gauge. The overall outer surface of the welded component and the weld area were visually inspected using the immersion method to observe whether any bubbles were overflowing to determine whether there were any signs of leakage. Three welded components were tested for each embodiment and comparative example.

[0149] Experimental results are shown in Table 2 below.

[0150] (3) Helium mass spectrometry detection: Experimental Method: A helium mass spectrometer leak detector was used for testing using the vacuum method (helium injection method). The air inlet 105 of the welded component was sealed to the detection port of the leak detector, and the exhaust port 106 was sealed with a plug. The internal cavity of the welded component was evacuated to a vacuum degree ≤1×10⁻⁶. -3 Pa, then helium gas was sprayed into the weld area and suspected areas on the outer surface of the component, and the helium gas signal entering the cavity was collected by a leak detector to measure the overall leakage rate. Three welded parts were taken for testing in each embodiment and comparative example.

[0151] Experimental results are shown in Table 2 below.

[0152] Table 2 Welding quality inspection results

[0153] As shown in Table 2: Examples 1-7: Average weld ratio ≥ 94.66%, average overall defect rate ≤ 31.03%, average proportion of flow channel and void defects approximately 25.43%. All three welded components in each example showed no pressure drop or leakage during the 2.5 MPa / 2h airtightness test, and the helium leakage rate was < 1 × 10⁻⁶. -10 Pa·m 3 / s, and the above measured data are all better than the design requirements (leakage rate ≤ 2 × 10). -10 Pa·m 3 / s, 2.2MPa without leakage). The reason is that the complete process of this application (activation + flash nickel plating + nickel-phosphorus layer) ensures the adhesion and thickness of the plating layer. During welding, the nickel-phosphorus layer forms an instantaneous liquid phase, which fully fills the interface defects and achieves low-temperature and high-density connection.

[0154] Comparative Example 1: No coating was formed. Direct butt welding of pure molybdenum with diffusion welding required a temperature of over 1700℃, and the interface contact was insufficient. The welding rate was only 34.35%, and the air tightness test could not be pressurized, resulting in a serious leakage rate exceeding the standard.

[0155] Comparative Example 2 (nickel-phosphorus layer replaced with nickel sulfamate layer, i.e. only 18.54μm nickel layer): The coating itself has qualified adhesion, thickness and appearance, but due to the lack of low melting point nickel-phosphorus layer, the instantaneous liquid phase cannot be formed at the welding temperature of 1200℃, the unwelded area of ​​the interface is large, the average welding rate is only 65.26%, and the air tightness test and leakage rate test are all unqualified.

[0156] Comparative Example 3 (omitting the flash nickel plating layer and directly electroless nickel-phosphorus plating): The nickel-phosphorus layer had extremely poor adhesion to the pure molybdenum substrate, the plating layer blistered and peeled off, the interface was severely contaminated during welding, the average welding rate was only 42.45%, and all leaks occurred during the airtightness test (0 / 3 passed).

[0157] Comparative Example 4 (activation treatment omitted): Residual oxide film caused a decrease in the adhesion of the nickel layer, blistering in some areas, uneven welding quality, and an average weld rate of 45.56%. All three welded parts failed the air tightness test (0 / 3 passed), but some areas showed some adhesion.

[0158] Comparative Example 5 (reverse plating treatment omitted during flash nickel plating): The nickel layer adhesion was slightly worse, but better than Comparative Example 3 and Comparative Example 4. Two of the three welded parts had a high welding rate and qualified air tightness (2 / 3), while only one had a qualified helium leakage rate (1 / 3), indicating that omitting the reverse plating treatment resulted in insufficient process stability.

[0159] In summary, the welding quality inspection data of Examples 1-7 all meet and exceed the design specifications (leakage rate ≤ 2 × 10⁻⁶). -10 Pa·m 3 The results (at / s and 2.2MPa with no leakage) verify the effectiveness and reliability of the technical solution presented in this application. Comparative examples, by omitting any of the key steps in activation, flash nickel plating, reverse plating, or electroless nickel-phosphorus plating, failed to obtain a satisfactory coating, thus affecting the subsequent welding quality. This demonstrates that the aforementioned pretreatment steps are synergistic and indispensable.

[0160] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.

[0161] Furthermore, it should be noted that the scope of the methods and apparatus in the embodiments of this application is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. In addition, features described with reference to certain examples may be combined in other examples.

[0162] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application.

Claims

1. A method for surface pretreatment before diffusion welding of pure molybdenum powder metallurgy parts, characterized in that, Includes the following steps: The pure molybdenum powder metallurgy parts to be processed undergo surface activation treatment; A nickel layer with a thickness of 1.5 μm to 3 μm is formed on the surface of a pure molybdenum powder metallurgy part after surface activation treatment. The nickel layer is a flash-plated nickel layer formed by electroplating. The electroplating solution contains nickel chloride and hydrochloric acid, with a nickel chloride concentration of 250 g / L to 350 g / L and a hydrochloric acid concentration of 4 g / L to 6 g / L. The electroplating process conditions are as follows: a reverse plating treatment is performed at a temperature of 20–30 °C before electroplating, and the reverse plating current density is 1 A / dm³. 2 ~2A / dm 2 The reverse plating time is 0.5 min to 1 min; then forward electroplating is performed at a temperature of 20 to 30℃ with a current density of 6 A / dm². 2 ~8A / dm 2 The electroplating time is 1 min to 2 min; A nickel-phosphorus layer is formed on the surface of the nickel layer of a pure molybdenum powder metallurgy part, the thickness of which is 12.5 μm to 18 μm. This nickel-phosphorus layer serves as a low-melting-point metal intermediate layer for diffusion welding. The nickel-phosphorus layer is formed by chemical plating. The plating solution includes nickel sulfate heptahydrate, sodium hypophosphite, sodium citrate, sodium acetate, and thiourea, wherein: the concentration of nickel sulfate heptahydrate is 30 g / L to 35 g / L, the concentration of sodium hypophosphite is 25 g / L to 30 g / L, the concentration of sodium citrate is 10 g / L to 15 g / L, the concentration of sodium acetate is 15 g / L to 20 g / L, and the concentration of thiourea is 0.5 mg / L to 1.5 mg / L. The chemical plating process conditions are: pH of the plating solution 4.8 to 5.2, adjusted with ammonia; plating solution temperature 90℃ to 92℃; and plating time 60 min to 80 min.

2. The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts according to claim 1, characterized in that, The mass fraction of phosphorus in the nickel-phosphorus layer is 8%-10%.

3. The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts according to claim 1, characterized in that, The activation treatment uses an activation solution containing hydrochloric acid and hexamethylenetetramine, with the concentration of hydrochloric acid being 150 g / L to 250 g / L and the concentration of hexamethylenetetramine being 3 g / L to 5 g / L; the activation treatment process conditions are: immersion at room temperature for 0.5 min to 1 min.

4. The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts according to claim 1, characterized in that, The process of activating pure molybdenum powder metallurgy parts also includes a water washing step, in which pure water is used for washing.

5. The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts according to claim 1, characterized in that, The process includes a water washing step after the nickel layer is formed, which uses pure water for washing.

6. The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts according to claim 1, characterized in that, After the nickel-phosphorus layer is formed, the process includes a water washing step and a drying step. The water washing step uses pure water for washing. The drying step is as follows: first, the surface of the pure molybdenum powder metallurgy part is dried by blowing it with clean compressed air. Then, it is placed in a vacuum oven for drying within an interval of no more than 60 minutes. The drying temperature is 200℃~220℃ and the time is 2 hours~3 hours. After drying, it is cooled to room temperature in a vacuum state and then removed from the furnace.

7. The surface pretreatment method for diffusion welding of pure molybdenum powder metallurgy parts according to claim 1, characterized in that, Before activating the pure molybdenum powder metallurgy parts, the process also includes surface cleaning of the pure molybdenum powder metallurgy parts to be treated. The surface cleaning process is as follows: organic solvent wiping, first water washing, ultrasonic chemical degreasing, second water washing, electrochemical degreasing, third water washing, water film continuity inspection, dust removal, and fourth water washing. The first wash, the second wash, the third wash, and the fourth wash all use pure water. The ultrasonic chemical degreasing process involves immersing pure molybdenum powder metallurgy parts in a chemical degreasing solution and applying ultrasonic waves for ultrasonic chemical degreasing treatment. The chemical degreasing solution is prepared using pure water and contains 30g / L to 50g / L sodium hydroxide, 20g / L to 40g / L sodium carbonate, and 20g / L to 40g / L trisodium phosphate. The ultrasonic chemical degreasing process conditions are: temperature controlled at 30℃ to 40℃ and time of 3min to 4min. The electrochemical degreasing process involves placing pure molybdenum powder metallurgy parts in an electrolyte as the anode for degreasing. The electrolyte consists of sodium hydroxide and pure water, with the sodium hydroxide concentration ranging from 30 g / L to 50 g / L. The electrochemical degreasing process conditions are: a temperature of 30°C to 40°C and a current density of 2 A / dm³. 2 ~5A / dm 2 The processing time is 2 to 3 minutes; The process for removing ash involves immersing pure molybdenum powder metallurgy parts in a mixed acid solution. The mixed acid solution is prepared from pure water and contains 100g / L to 150g / L of nitric acid and 100g / L to 150g / L of sulfuric acid. The process conditions for removing ash are: treatment at room temperature for 0.5min to 1min.

Citation Information

Patent Citations

  • Molybdenum alloy fusion welding method based on microalloying and synchronous parasitic brazing

    CN107008985A

  • Surface modifying method of molybdenum material

    CN110257864A

  • Periodic chromium plating method for improving corrosion resistance of chromium layer of workpiece

    CN120625128A

  • Hard alloy composite roller process

    CN120791107A